2012
DOI: 10.1590/s0036-36342012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Youth who neither study nor work: mental health, education and employment

Abstract: Objective. Limited educational and job opportunities for youth has led to a phenomenon termed NEET (not in education, employment or training). The objective is to estimate the prevalence of psychiatric disorders, substance use and suicidal behavior in youth classified as NEET and to compare with those who study only, work only or do both. Material and Methods. 3 005 12-to-17 year-olds in Mexico City were evaluated in 2005 with the Composite International Diagnostic Interview. Descriptive and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
96
2
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 20 publications
8
96
2
12
Order By: Relevance
“…This is congruent with other studies of work and study outcomes in young people which has also identified gender, educational attainment, socioeconomic background, recent cannabis use and, as previously discussed, family history of schizophrenia or bipolar disorder (Benjet et al, 2012;O'Dea et al, 2014). Prior research specific to help-seeking young people also identified being male and recent cannabis use (O'Dea et al, 2014).…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 87%
“…This is congruent with other studies of work and study outcomes in young people which has also identified gender, educational attainment, socioeconomic background, recent cannabis use and, as previously discussed, family history of schizophrenia or bipolar disorder (Benjet et al, 2012;O'Dea et al, 2014). Prior research specific to help-seeking young people also identified being male and recent cannabis use (O'Dea et al, 2014).…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 87%
“…Odds ratios for substance abuse are 3.5 times higher for adolescents that are not enrolled in the school system and are unemployed as compared to those that are full-time students (Benjet et al, 2012). As in other countries, availability of substances, low perception of risk, having friends and siblings using drugs increase the risk of experimentation and continuous use (Villatoro et al, 2012).…”
Section: The Drug Scene In Mexico and The Road Aheadmentioning
confidence: 99%
“…Furthermore, a few previous studies associated NEET phenomenon with increased mental health issues, including conduct disorders, mood disorder, and suicidal thoughts [3,4]. However, causal paths from mental health to NEET phenomenon are not clear.…”
mentioning
confidence: 99%
“…In 2011, the prevalence rate of NEET youth across Organization for Economic Cooperation and Development (OECD) countries was 16% among the 15e29 year olds (7% inactive and 9% unemployed) and 20% among the 25e29 year olds (12% inactive and 8% unemployed) [2]. Public health literature has recently shown interest in this phenomenon because NEET youth may be a vulnerable and socially excluded subgroup of youth, with increased risky behaviors and poor mental health [3,4]. The at-risk population includes school dropouts, minorities, foster youth, and youth in the justice sys-tem.…”
mentioning
confidence: 99%
See 1 more Smart Citation